Pengaruh Kecerdasan Spiritual dan Minat Belajar Terhadap Motivasi Belajar Siswa Kelas X Pada Mata Pelajaran Ekonomi - Rimelvi Rimelvi; Dessi Susanti (Universitas Negeri Padang, 2020)
This study aims to determine: 1) the effect of spiritual intelligence on class X students' motivation to study economics in state high school 3 Padang. 2) the effect of interest in learning on class X students' learning motivation on economics in state high school 3 Padang. 3) the effect of spiritual intelligence and interest in learning together on class X students' motivation to study economics in state high school 3 Padang. This type of research is quantitative research with a causative descriptive method. The population in this study amounted to 323 with sampling using proportional simple random sampling techniques. In order to obtain a sample of 179 class X students. Data collection techniques using a research questionnaire. The collected data were analyzed using multiple regression analysis. Based on the results of the study found: 1) spiritual intelligence has a positive and significant effect on learning motivation of class X students in economic subjects at SMA Negeri 3 Padang seen from the value of sig. 0,000 < 0.05. 2) interest in learning has a positive and significant effect on student motivation in class X in economic subjects in SMA Negeri 3 Padang seen from the sig. 0,000 < 0.05. 3) spiritual intelligence and interest in learning together have a positive and significant effect on learning motivation of class X students in economic subjects at SMA Negeri 3 Padang seen from the value of sig. 0,000 < 0.05.Keywords: Kecerdasan Spiritual, Minat Belajar, Motivasi Melajar